Phytochemical and Bioinformatic Studies of Citrus Flavonoids as Chemopreventive Agents Targeting GGPS1 for Liver Cancer - Wardani, Ratih Kurnia; Rhamandana, I Made; Gono, Christina Mutiara Putri; Ikawati, Muthi (Indonesian Journal of Cancer Chemoprevention, 2021)
Overexpression of geranylgeranyl diphosphate synthase 1 (GGPS1) is an unfavorable prognosis in liver cancer development. The side effects of therapeutic standards encourage the development of therapeutic agents from herbal materials. Citrus peels are rich of phytochemical compounds, especially citrus flavonoids, that possess cytotoxic activities. This study aimed to determine the potential of citrus flavonoids as chemopreventive agents targeting GGPS1 protein by phytochemical and bioinformatic studies. Dried peels of Citrus reticulata were extracted by hydrodynamic-cavitation method followed by identification of compounds using thin layer chromatography (TLC). The expression level of GGPS1 was obtained from UALCAN, while its correlation with survival rate was obtained from the GEPIA. Prediction models regarding the potential inhibitors of citrus peel compounds against GGPS1 were obtained through KNIME and ChEMBl, followed by literature studies on chemopreventive activity of citrus flavonoids. The molecular docking was used to predict the molecular interaction followed by tracking of target genes that were positively correlated with GGPS1 by SwissTargetPrediction. Yielded 75% (v/v), the extract positively contained citrus flavonoid with hesperidin as comparison. Overexpression of GGPS1 significantly reduced the survival rate of liver cancer patients (p value=0.019). Four citrus flavonoid compounds, namely tangeretin, nobiletin, hesperidin, and naringenin showed potential inhibition to GGPS1. The molecular docking showed that tangeretin had a strong affinity compared to the native ligand and zoledronic acid, as positive control. PARP1, CSNK2A1, TNKS2, and GSK3B were clarified as targeted genes for tangeretin and nobiletin that positively correlated with GPPS1. In vitro and in vivo studies will validate our findings and support the development of citrus peel extract with rich flavonoid contents as a chemopreventive agent.Keywords: geranylgeranyl diphosphate synthase 1 (GGPS1), liver cancer, hydrodynamic-cavitation, citrus flavonoid, bioinformatic.